2022
DOI: 10.3389/fvets.2022.887746
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of the renal size using a kidney length to vertebral body length ratio in cats

Abstract: Ultrasonographic assessment of the renal size can provide useful clinical information, in combination with other ultrasonographic parameters. The aims of this study were to establish the agreement between the ultrasonographic and radiographic measurements of the kidneys (K) and vertebral bodies (L5 and L6), to establish an ultrasonographic measurement of kidney-to-vertebral body (L5 and L6) ratio to estimate the renal size in cats, and to assess the impact of age, body weight, sex, and gonadal status on the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…The long dimension of the left kidney is normal at 3.7 cm (Figure 12). This dimension is within the normal range (3.0-4.3 cm), as the sonograms that previous studies have reported (Dennis, 2010;Martinez et al, 2022;Penninck & d'Anjou, 2022). The result of ultrasonography of the right kidney showed a normal appearance of the capsule, cortex, and medulla.…”
Section: Ultrasonographysupporting
confidence: 84%
See 1 more Smart Citation
“…The long dimension of the left kidney is normal at 3.7 cm (Figure 12). This dimension is within the normal range (3.0-4.3 cm), as the sonograms that previous studies have reported (Dennis, 2010;Martinez et al, 2022;Penninck & d'Anjou, 2022). The result of ultrasonography of the right kidney showed a normal appearance of the capsule, cortex, and medulla.…”
Section: Ultrasonographysupporting
confidence: 84%
“…The boundary between the cortex and medulla of the right kidney was clear, with no abnormalities. The long dimension of the right kidney was normal (3.4 cm) (Figure 13), and it is within the normal range (3.0-4.3 cm) (Dennis, 2010;Martinez et al, 2022;Penninck & d'Anjou, 2022). However, the ureteral diameter of the right kidney was 1.6 mm.…”
Section: Ultrasonographymentioning
confidence: 92%
“…Pada hasil X-ray tidak ada urolit pada kandung kemih dan ukuran ginjal normal yaitu 35,2 mm (nilai normal 30-45 mm, Martinez et al, 2022).…”
Section: Hasil Pemeriksaan Radiografiunclassified